Student Perceptıons of Open Unıversıty Servıces ın the Islands Regıon: A Study ın Selayar Islands Regency, Indonesıa - Jalil Jalil; Kusmaladewi Kusmaladewi; Makkatenni Makkatenni; Muhammad Alwi; Muh Ali Alimuddin (Universitas Cokroaminoto Palopo, 2024)
The main issue of this research is to explore students' perceptions of the key strengths of Universitas Terbuka in implementing distance education, specifically related to flexibility, affordability, interaction, accessibility, and distance learning skills in the Selayar Islands Regency. The present study aims to delve into student perception of the key strengths of Universitas Terbuka that become the standards by which its endeavors of distance education are carried out. Adopting a descriptive quantitative method, the study gathered data using a questionnaire in which five variables were measured, i.e., flexibility, affordability, interaction, accessibility, and distance-learning skills. The 5-point scale questionnaire was created in Google Forms and was distributed to the whole student population of Universitas Terbuka in Selayar Islands Regency through Study Groups. The data from the student questionnaire was assessed using a descriptive statistical method in SPSS 20. Based on the descriptive statistic findings from a total of 48 questionnaires, the mean that stands for the student perception of the five variables is 4.37 for flexibility, 4.34 for affordability, 4.35 for interaction, 4.45 for accessibility, and 4.31 for distance-learning skills. These findings lead to a noticeable conclusion; Universitas Terbuka has mobilized education and reached out to remote learners in small islands in an effective manner. In turn, this potentially informs policy discussions as to improve the roles of Universitas Terbuka in extending educational opportunities and services for underprivileged rural communities that particularly suffer from low educational attainment.